2D Layered α‐Fe2O3/rGO Flexible Electrode Prepared through Colloidal Electrostatic Self‐Assembly. Issue 8 (23rd May 2017) - Zhang, Huifang; Lu, Chunxiang; Chen, Chengmeng; Xie, Lijing; Zhou, Pucha; Kong, Qingqiang
Abstract: Through the simple hydrolysis of FeCl3 in boiling water, Fe(OH)3 colloidal nanoparticles (NPs) can be achieved that exhibit a highly positively charge. Graphene oxide (GO) nanosheets are negatively charged when dispersed in water. Inspired by these fascinating characteristics, a 2D layered α‐Fe2 O3 /rGO hybrid film (FGHF) was fabricated through colloidal electrostatic self‐assembly with subsequent vacuum filtration and hydrothermal reduction. In this hybrid film, cubical α‐Fe2 O3 NPs are well‐distributed on rGO sheets, which can provide sufficient active interfacial sites and effectively alleviate the volume variation of α‐Fe2 O3 NPs during electrochemical reactions. The as‐obtained FGHF exhibits a high specific capacitance of 714 F g −1 and an outstanding rate capability of 42.6 % retention at 30 A g −1 . Moreover, a flexible supercapacitor was fabricated, which can achieve a high volumetric capacitance of 16.45 F cm −3, leading to an energy density of 1.46 mWh cm −3 and a power density of 199.8 mW cm −3 . The flexible nature of the FGHF allows the as‐fabricated supercapacitor to remain undamaged with almost no change in capacitive performance when bending up to 180°. Abstract : Through the static : A 2D layered α‐Fe2 O3 /rGO hybrid film can be prepared through colloidal electrostatic self‐assembly with subsequent vacuum filtration and hydrothermal reduction. The layer‐by‐layer hybrid film electrode exhibits a high specific capacitance of 714 F g −1 at a current density of 1 A g −1 . When assembled into an all‐solid‐state flexible symmetric supercapacitor, a high volumetric capacitance of 16.45 F cm −3, volumetric energy density of 1.46 mWh cm −3, and volumetric power density of 199.8 mW cm −3 can be obtained.